2015
DOI: 10.1097/qai.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Weight Evolution Among HIV-Positive Patients Initiating Antiretroviral Treatment in Low-Resource Settings

Abstract: Background In resource limited settings clinical parameters, including body weight changes, are used to monitor clinical response. Therefore we studied body weight changes in patients on antiretroviral treatment (ART) in different regions of the world. Methods Data were extracted from the “International Epidemiologic Databases to Evaluate AIDS”, a network of ART programmes that prospectively collects routine clinical data. Adults on ART from the Southern-, East-, West- and Central African and the Asia-Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
5
14
0
Order By: Relevance
“…When compared with patients at WHO stage I, those at WHO stages III and IV have decreased BMI. This finding is in line with a multicentre study in resource-limited settings which shows individuals who had high clinical status (WHO stages III and IV) had poorer weight gain when compared with weight change in patients at lower WHO stage 14. The possible reason can be unexplained chronic diarrhoea and HIV enteropathy in these patients and the associated malabsorption4 or it could be due to fever of unknown origin in the late stage of the disease which results in an increased calorie loss and wasting 30…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When compared with patients at WHO stage I, those at WHO stages III and IV have decreased BMI. This finding is in line with a multicentre study in resource-limited settings which shows individuals who had high clinical status (WHO stages III and IV) had poorer weight gain when compared with weight change in patients at lower WHO stage 14. The possible reason can be unexplained chronic diarrhoea and HIV enteropathy in these patients and the associated malabsorption4 or it could be due to fever of unknown origin in the late stage of the disease which results in an increased calorie loss and wasting 30…”
Section: Discussionsupporting
confidence: 90%
“…The BMI of patients with HIV is affected by gender,14 duration of treatment,10 15 16 isoniazid prophylaxis therapy (IPT) and cotrimoxazole prophylaxis therapy (CPT),17 18 WHO stage14 and CD4 count 15 19…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more frequent contact with the health care system due to chronic HIV care may provide opportunities for reinforcement of health care messages on the importance of maintaining a healthy weight [40]. Finally, different antiretroviral therapies may also have differing effects on weight [41]. Lower BMI with problematic alcohol consumption may be due to the chronic malnutrition that can occur with excess alcohol intake [42].…”
Section: Discussionmentioning
confidence: 99%
“…Confusing the interpretation is the fact that lipid changes may not be a direct consequence of ART but rather signify a return to health induced by successful ART and associated weight gain, with increase in body fat driving metabolic changes as found in the general population. This is supported by studies indicating that weight increase is correlated with increased CD4 count (3). A recent dual energy X-ray absorptiometry (DXA) -scan substudy of ACTG 5257 showed that darunavir/ritonavir (DRV/r), atazanavir/ritonavir (ATV/r) and raltegravir (RAL) (all combined with tenofovir [TDF]/ emtricitabine [FTC]) were associated with the same degree of visceral fat accumulation (4).…”
Section: Introductionmentioning
confidence: 90%